2004
DOI: 10.1191/0961203303lu1002oa
|View full text |Cite
|
Sign up to set email alerts
|

A deficiency of CD4+ CD25+ T cells permits the development of spontaneous lupus-like disease in mice, and can be reversed by induction of mucosal tolerance to histone peptide autoantigen

Abstract: It has been repeatedly shown that a subset of CD4+ T cells that constitutively express CD25 on their surface plays a role in the maintenance of self-tolerance. They may directly or indirectly affect the development of autoimmunity in susceptible mice and humans. In this study, we examine the relationship between the percentage of peripheral CD4+CD25+ T cells and the state of disease in spontaneous models of autoimmune disease. We found that both BWF1 and SNF1 mice that spontaneously develop a lupus-like diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
63
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 24 publications
2
63
0
Order By: Relevance
“…In other studies, CD4 + CD25 + cells were found to be decreased in patients with active disease when compared to controls and patients without active disease [45]. Wu and Staines [46] reported that a deficiency in CD4 + CD25 + T cells contributed to the susceptibility to develop spontaneous lupus disease.…”
Section: Discussionmentioning
confidence: 89%
“…In other studies, CD4 + CD25 + cells were found to be decreased in patients with active disease when compared to controls and patients without active disease [45]. Wu and Staines [46] reported that a deficiency in CD4 + CD25 + T cells contributed to the susceptibility to develop spontaneous lupus disease.…”
Section: Discussionmentioning
confidence: 89%
“…Lupus patients appear to have a reduced frequency of Treg cells [6,7]. Likewise, in some murine models of SLE Treg cells are diminished and/or have reduced Foxp3 protein expression [8][9][10]. In contrast, 16-20 week old C3H gld/gld mice have an increased frequency of Foxp3 + T cells with Foxp3 protein expressed at levels similar to normal mice [11].…”
Section: Introductionmentioning
confidence: 94%
“…Interestingly, a significantly reduced level of Treg has also been observed to correlate with autoantibody production and the onset of a lupus-like disease in different murine models (18,19). However, analysis of the role of Treg in human autoimmunity during ongoing disease has been hampered by a lack of specific antibodies, because all available Treg-"specific" surface markers (CD25, CTLA-4, glucocorticoid-induced tumor necrosis factor [TNF] receptor) can also be expressed on nonsuppressive activated T cells.…”
mentioning
confidence: 99%